ESG Rating and Financial Performance: A Comparison Between State-Owned and Non-State-Owned Sectors in the Chinese Stock Market - Yan,Yaqian; Li,Huiyang (2024)
Following the adoption of the "double carbon" policy in China, the concept of Environmental, Social, and Governance (ESG) has gained considerable attention within the Chinese market, significantly impacting investor decision-making. This thesis examines the impacts of ESG principles on the overall financial performance of investment portfolios. Through the classification of Chinese A-listed firms into High, Medium, and Low ESG groups, corresponding portfolios are constructed for in-depth analysis. To comprehensively assess the financial performance of these portfolios in relation to ESG, three key metrics—Jensen’s alpha, Expected Shortfall, and Sharpe ratio—are selected. By employing the Fama-French Five-Factor model, we uncover that all portfolios exhibit negative alpha, indicating underperformance relative to expected returns based on the model's risk factors. Notably, the High ESG portfolio demonstrates the most significant degree of underperformance, coupled with the lowest Sharpe ratio among all portfolios. The positive expected shortfall of the High Minus Low ESG portfolio highlights the heightened extreme losses experienced by high ESG portfolios compared to their low ESG counterparts. These findings suggest a prevailing preference among investors in the Chinese market for higher ESG scores over superior financial performance following the adoption of the "double carbon" policy. Furthermore, our analysis delves into the distinction in the impact of ESG ownership on the financial performance of portfolios. We identify a notable divergence, with state-owned companies exhibiting no significant excess return over the market, while non-state-owned companies demonstrate a significantly negative Jensen’s alpha. Additionally, High ESG portfolios consistently underperform compared to Low ESG portfolios in terms of the Sharpe ratio. Finally, we observe that private ownership generally entails higher risk, as evidenced by elevated VaR and ES/CVaR values across all ESG portfolios.
Keywords: ESG; Portfolio choice; Ownership; Financial performance